Afeksi dan Kesadaran Politik Perempuan Pekerja Migran Indonesia - Widiantini, Ikhaputri; Manalu, Abby Gina Boang Manalu (Yayasan Jurnal Perempuan, 2024)
The problems experienced by Indonesian female migrant workers both in their own country and in the destination country show how vulnerable they are to violence. Most of them are workers in the informal sector such as domestic and care workers, who are categorized as low-skilled workers. As a result of this categorization, they often experience discrimination and even violence. This is the impact of neglecting experiences, especially in fulfilling political rights, which hinders full access to policy guarantees that protect them. Data were collected using literature analysis and secondary research. This study uses a philosophical approach based on Sara Ahmed’s theory of affection and Nancy Fraser’s recognition of how the experiences of Indonesian female migrant workers need to include empathetic emotional values and recognition of the political rights of Indonesian female migrant workers. The findings of this article highlight the importance of fostering political awareness through the integration of affection and recognition in understanding and overcoming the political injustice of Indonesian female migrant workers.